LEKSIKON ARSITEKTUR RUMAH ADAT KAMPUNG NAGA: KAJIAN ETNOSEMANTIK - Hendri Gunawan; Vira Maulani; Prasasti Dwi Putri; Muhammad Rizki Periandi; Ayu Yulianti; Odien Rosidin; Muhammad Rinzat Iriyansah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
Sundanese traditional houses have their own peculiarities in architecture and philosophical values that are very meaningful, such as the traditional house in Naga Village. Naga Village still maintains the typical Sundanese traditional architecture in its buildings, by having a very unique architecture. Thus, this study has the objectives to: (1) describe the traditional house of Kampung Naga, (2) describe the lexicon of tools and materials of traditional houses of Kampung Naga, and (3) describe the lexicon of the construction of traditional houses of Kampung Naga Village. This study uses a qualitative descriptive method to describe the findings of the architectural lexicon of traditional houses in Naga Village. Research data was obtained through observation, interview, documentation, and literature study methods. Furthermore, the data was analyzed using interpretation techniques by sorting out data according to the research subject in the form of traditional houses in Naga Village. The results of the study found that the traditional house of Kampung Naga was built in the form of a stage to adapt to the hilly geographical conditions and have high humidity. The shape and construction of the house are determined by customary rules, a certain time, and harmony with nature. In its construction, tools and materials are obtained from the surrounding nature. Traditional houses are built in cooperation by the community. However, there is a special craftsman named Dulah who has special skills. After conducting the analysis, the researcher found twelve lexicons of tools and materials of the Naga Village traditional house, including: bedog, tatah, palu kai, di-pen, bendo, and others . As for the lexicon of the building of the Naga Village traditional house, there are six lexicons consisting of golodog, goah, kolong, panggangsao, pawon, and suhunan.